Synthesis, Characterization and Pharmacological Evaluation of 2-Substituted thieno[2,3-d]pyrimidine-4(3H)-ones - SHIROLE, N.L.; SHIROLE, K.D.; DEORE, R.D.; FURSULE, R.A.; TALELE, G.S. (Asian Journal of Chemistry, 2010)
A series of 2-piperazinyl and substituted piperazinylthieno[2,3- d]pyrimidines (Ia-j) are synthesized for antihistaminic activity through the reaction of piperazine and N-substituted piperazines with corresponding 2-methylthio and 2-chloromethylthieno[2,3- d]pyrimidine-4(3H)-ones. The compounds were evaluated for H1-receptor antagonists in vitro, by guinea pig ileum isotonic contraction method. The compounds Ic, Id and If, exhibited most significant activities amongst all the evaluated compounds and total six compounds were much superior to diphenhydramines (higher pA2 values). The synthesized compounds also exhibited much lower sedative potential compared to the standard drug.